Beyond the Walls: Establishing Classroom Expectations in a Virtual Classroom - Croce, Katharine M.; Salter, Jamie S. (Frontiers in Education, 2022)
Classroom expectations are clearly defined explanations of behavioral and classroom performance that help create a consistent and safe learning environment (Grossman, 2004). The value of setting classroom expectations has been researched for nearly 60 years and researchers have consistently found that teachers who explicitly teach expectations have students who are: on-task at higher rates, have more prosocial behaviors with peers, and overall are more academically successful than children who have not been systematically taught classroom expectations (Hester, 2009). Setting expectations is a way to define appropriate classroom behavior and to build consistency and structure among students (Baer, 2005). As result of the COVID-19 pandemic, many classrooms around the globe are experiencing higher rates of behavioral challenges than pre-pandemic levels (National Association for School Psychologists (NASP), 2021). Costello et al. (2003), determined that during a typical school trajectory, approximately 20% of children experience some social–emotional and behavioral (SEB) concern. NASP (2021) now expects these rates to double or triple after the COVID-19 pandemic. Educators are mandated to implement evidenced-based practices (Individuals with Disabilities Education Improvement Act, 2004) and therefore, should further explore the implementation of setting expectations while their students are engaged in virtual learning, hybrid learning, and/or returning to the brick-and-mortar classroom amidst the pandemic. The purpose of this article is to demonstrate that systematically teaching expectations to all students in a virtual setting is an innovative and effective teacher classroom practice that can then be carried into the brick-and-mortar classroom as students return to in-person learning.